2013
DOI: 10.1371/journal.pone.0069681
|View full text |Cite
|
Sign up to set email alerts
|

A New Omics Data Resource of Pleurocybella porrigens for Gene Discovery

Abstract: Background Pleurocybella porrigens is a mushroom-forming fungus, which has been consumed as a traditional food in Japan. In 2004, 55 people were poisoned by eating the mushroom and 17 people among them died of acute encephalopathy. Since then, the Japanese government has been alerting Japanese people to take precautions against eating the P . porrigens mushroom. Unfortunately, despite efforts, the molecular mechanism of the encephalopathy remains elusive. The genome and transcriptome sequence data of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…Publically available non-Salix RNA-seq data used for forced mapping were acquired from Homo sapiens (human, EBI: PRJEB6971); Pleurocybella porrigens (angel wing fungi, EBI: DRR003995; EBI: DRR003996; Suzuki et al, 2013); Carassius auratus (goldfish, EBI: DRR014529; Abe et al, 2014); Oryza sativa (rice, EBI: SRR611648); and Mammuthus primigenius (woolly mammoth; DNA-seq, EBI: SRR2009641; EBI SRR2009644; Lynch et al, 2015).…”
Section: Mapping To a Reference Genomementioning
confidence: 99%
“…Publically available non-Salix RNA-seq data used for forced mapping were acquired from Homo sapiens (human, EBI: PRJEB6971); Pleurocybella porrigens (angel wing fungi, EBI: DRR003995; EBI: DRR003996; Suzuki et al, 2013); Carassius auratus (goldfish, EBI: DRR014529; Abe et al, 2014); Oryza sativa (rice, EBI: SRR611648); and Mammuthus primigenius (woolly mammoth; DNA-seq, EBI: SRR2009641; EBI SRR2009644; Lynch et al, 2015).…”
Section: Mapping To a Reference Genomementioning
confidence: 99%
“…To disclose the genes underlying the poisonings and provide mechanistic insight, we have sought to develop an information infrastructure containing omics data. In a previous study, we sequenced the genome and transcriptome of the mushroom using next-generation sequencing techniques [ 12 ]. That study revealed that, compared to other Agaricales, the genome of the angel’s wing had a unique structure and contained numerous novel genes.…”
Section: Resultsmentioning
confidence: 99%
“…The recent advances in crop genomics, particularly the use of high throughput next-generation sequencing (NGS) technologies, look promising to identify causal genetic factors at genome by sequencing the whole genome and transcriptome of a species. As a result, the complete gene catalogue of a crop species and functional genes in different tissues could be identified besides allowing studying the genetic pathways involved in growth and development and biochemical pathways that eventually could be correlated with the crop phenotypes [1,2]. Furthermore, the sequence data generated in vast amount provide a basis of genetic variation such as singlenucleotide polymorphisms (SNPs), which ultimately provide a relationship between genotype and phenotype in different species.…”
Section: Introductionmentioning
confidence: 99%